Mitogen activated protein kinase phosphatase-1 prevents the development of tactile sensitivity in a rodent model of neuropathic pain - Ndong Christian; Landry Russell P; DeLeo Joyce A; Romero-Sandoval Edgar (SAGE Publishing, 2012)
Abstract Background Neuropathic pain due to nerve injury is one of the most difficult types of pain to treat. Following peripheral nerve injury, neuronal and glial plastic changes contribute to central sensitization and perpetuation of mechanical hypersensitivity in rodents. The mitogen activated protein kinase (MAPK) family is pivotal in this spinal cord plasticity. MAPK phosphatases (MKPs) limit inflammatory processes by dephosphorylating MAPKs. For example, MKP-1 preferentially dephosphorylates p-p38. Since spinal p-p38 is pivotal for the development of chronic hypersensitivity in rodent models of pain, and p-p38 inhibitors have shown clinical potential in acute and chronic pain patients, we hypothesize that induction of spinal MKP-1 will prevent the development of peripheral nerve-injury-induced hypersensitivity and p-p38 overexpression. Results We cloned rat spinal cord MKP-1 and optimize MKP-1 cDNA in vitro using transfections to BV-2 cells. We observed that in vitro overexpression of MKP-1 blocked lipopolysaccharide-induced phosphorylation of p38 (and other MAPKs) as well as release of pro-algesic effectors (i.e., cytokines, chemokines, nitric oxide). Using this cDNA MKP-1 and a non-viral, in vivo nanoparticle transfection approach, we found that spinal cord overexpression of MKP-1 prevented development of peripheral nerve-injury-induced tactile hypersensitivity and reduced pro-inflammatory cytokines and chemokines and the phosphorylated form of p38. Conclusions Our results indicate that MKP-1, the natural regulator of p-p38, mediates resolution of the spinal cord pro-inflammatory milieu induced by peripheral nerve injury, resulting in prevention of chronic mechanical hypersensitivity. We propose that MKP-1 is a potential therapeutic target for pain treatment or prevention.